A filter microplate assay for quantitative analysis of DNA-binding proteins using fluorescent DNA - Yang, William C. (2011)
We present a rapid method for quantifying the apparent DNA binding affinity and capacity of recombinant transcription factors (TFs). We capture His(6)-tagged TFs using Ni-NTA agarose and incubate the immobilized TFs with fluorescently-labeled cognate DNA probes. After washing, the strength of the fluorescence signal indicates the extent of DNA binding. The assay was validated using two pluripotency-regulating TFs, SOX2 and NANOG. Using competitive binding analysis with non-labeled competitor DNA, we show that SOX2 and NANOG specifically bind to their consensus sequences. We also determined the apparent affinity of SOX2 and NANOG for their consensus sequences to be 54.2±9 nM and 44.0±6 nM, respectively, in approximated agreement with literature values. Our assay does not require radioactivity, but radioactively labeling the TFs enables the measurement of absolute amounts of immobilized SOX2 and NANOG, and hence a DNA to protein binding ratio. SOX2 possesses a 0.95 DNA to protein ratio while NANOG possesses a 0.44 ratio, suggesting that most of the SOX2 and approximately half of the NANOG are competent for DNA binding. Alternatively, the NANOG dimer may be capable of binding only one DNA target. This flexible DNA binding assay enables the analysis of crude or purified samples with or without radioactivity.